Estimated number of N95 respirators needed for healthcare workers in acute-care hospitals during the coronavirus disease 2019 (COVID-19) pandemic. (11th November 2021) - Wedlock, Patrick T.; O'Shea, Kelly J.; Conte, Madellena; Bartsch, Sarah M.; Randall, Samuel L.; Ferguson, Marie C.; Cox, Sarah N.; Siegmund, Sheryl S.; Kulkarni, Sarah; Nash, Denis; Lin, Michael Y.; Lee, Bruce Y.
Abstract: Objective: Due to shortages of N95 respirators during the coronavirus disease 2019 (COVID-19) pandemic, it is necessary to estimate the number of N95s required for healthcare workers (HCWs) to inform manufacturing targets and resource allocation. Methods: We developed a model to determine the number of N95 respirators needed for HCWs both in a single acute-care hospital and the United States. Results: For an acute-care hospital with 400 all-cause monthly admissions, the number of N95 respirators needed to manage COVID-19 patients admitted during a month ranges from 113 (95% interpercentile range [IPR], 50–229) if 0.5% of admissions are COVID-19 patients to 22, 101 (95% IPR, 5, 904–25, 881) if 100% of admissions are COVID-19 patients (assuming single use per respirator, and 10 encounters between HCWs and each COVID-19 patient per day). The number of N95s needed decreases to a range of 22 (95% IPR, 10–43) to 4, 445 (95% IPR, 1, 975–8, 684) if each N95 is used for 5 patient encounters. Varying monthly all-cause admissions to 2, 000 requires 6, 645–13, 404 respirators with a 60% COVID-19 admission prevalence, 10 HCW–patient encounters, and reusing N95s 5–10 times. Nationally, the number of N95 respirators needed over the course of the pandemic ranges from 86 million (95% IPR, 37.1–200.6 million) to 1.6 billion (95% IPR, 0.7–3.6 billion) as 5%–90% of the population is exposed (single-use). This number ranges from 17.4 million (95% IPR, 7.3–41 million) to 312.3 million (95% IPR, 131.5–737.3 million) using each respirator for 5 encounters. Conclusions: We quantified the number of N95 respirators needed for a given acute-care hospital and nationally during the COVID-19 pandemic under varying conditions.